Pembangunan sosial melalui program pembasmian kemiskinan: kajian perbandingan antara kes di Melaka, Malaysia dan kes di Riau, Indonesia / Mohamad Zahir Zainudin - Mohamad Zahir, Zainudin (2016)
Social development is part of the contributors to the country's progress. Economic development framework underlying the progress of the world over the past five decades increasingly aligned with the social development framework for huge implications on human development and the environment. The emphasis on social development that began around the 1980's was seen as vital for the sustainability and progress of a country. The patterns of governance in Malaysia and Indonesia affect social development of both countries. Different social situations based on the total population, the changes and trends in the history of development of the country. This difference exists because poverty eradication strategies made by both countries to move on uneven stage. Prolonged debate exists concerning the effectiveness of anti-poverty programs through micro-credit to the well-being of the poor. Some studies show microcredit have positive impact to the poor people's lives. However, other studies stated that what actually seemed as a remedy is actually just an increase in the business income that does not necessarily bring about to a better well-being of the poor. This research identifies the impact of the implementation of social interventions brought in through microcredit schemes of poverty alleviation programs for the welfare being of society in Malaysia and Indonesia. The methodology used was a combination of the quantitative and qualitative methods aimed to get the maximum results. Data analysis performed on the respondents indicated four factors leading to the failure of the welfare of the community. These factors are social networks, community participation, community development and employment opportunities. This research suggests that agencies involved in poverty alleviation through microcredit schemes must carry out appropriate efforts towards the empowerment and active participation of the respondents in social and economic investment as stated in the Standard Model of Social Development.